Heavy resistance exercise training in older men: A responder and inter-individual variability analysis - Casper Soendenbroe; Jesper L. Andersen; Mette F. Heisterberg; Michael Kjaer; Abigail L. Mackey (PLoS ONE, 2026)
Background The extent of inter-individual variability in response to heavy resistance exercise training (HReT), and the possible existence of non-responders, remains unclear. This study aimed to determine the degree of variability in response to prolonged HReT in healthy older men. Methods We conducted a secondary analysis of an 8- and 16-week intervention involving thrice-weekly HReT (EX) or continuation of a sedentary lifestyle (SED). Fifty-eight healthy men (age 72 ± 5) were randomized to EX (n = 38) or SED (n = 20). Assessments were conducted at baseline, 8-weeks, and 16-weeks for five outcomes: maximal voluntary contraction strength (MVC), rate of force development (RFD), quadriceps cross-sectional area (qCSA), and type I and II myofibre cross-sectional area (fCSA). Inter-individual variability was assessed using the standard deviation of individual responses (SD IR ). Individual changes relative to a Typical Error were used to classify responders as Poor, Trivial, Robust, or Excellent. Results 16 weeks of EX led to group-level increases in MVC (19 ± 14%), RFD (58 ± 80%), qCSA (3 ± 4%), and type II fCSA (14 ± 25%), with no changes in SED. Substantial inter-individual variability was observed. After 16 weeks, 82% of EX participants were classified as Robust or Excellent responders; only 5% were Poor responders. Training compliance and 1RM progression did not explain this variability. Lower baseline levels were linked to greater improvements but did not fully account for response differences. Conclusions This study provides strong evidence of inter-individual variability in response to HReT among healthy older men. Given the rarity of true non-responders, our data support HReT as the universally recommended first-line strategy for enhancing muscle mass and strength.